Establishing Potential Bilateral Investment Treaty Between Indonesia and Japan to Bridge IJEPA - Muhammad Syabil Baykhaqi; Siti Anisah (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
The bilateral investment relationship between Indonesia and Japan has been crucial in fostering economic cooperation, particularly under the Indonesia-Japan Economic Partnership Agreement (IJEPA). However, IJEPA which has been enforced since 2008 has encountered implementation challenges, such as specificity in addressing modern investment challenges, regulatory changes, environmental concerns, and labor mobility, particularly in the caregiving sector. This research explores the possibility of establishing a Bilateral Investment Treaty (BIT) between Indonesia and Japan to bridge the gaps within IJEPA and strengthen bilateral investment relations. The research employs a normative legal approach, to analyze legal documents, treaties, and secondary sources to assess the feasibility of a potential BIT in bridging IJEPA. The study identifies key principles that should be included in the proposed BIT, such as clear definitions of Fair and Equitable Treatment (FET), Most-Favored-Nation (MFN) clauses, and dispute resolution mechanisms that balance investor protection with state sovereignty. Additionally, the thesis highlights the importance of sector-specific provisions tailored to the automotive industry, labor mobility (especially for caregivers), and green energy projects, which align with the strategic interests of both nations. The findings suggest that a new BIT between Indonesia and Japan is both feasible and necessary to enhance bilateral investment relations. The proposed treaty would provide greater legal certainty, encourage long-term investment, and address the shortcomings of IJEPA. By incorporating updated provisions on investor protection, labor rights, and sustainable development, the BIT would foster a more stable and predictable investment environment, benefiting both countries economically and socially.